2002
DOI: 10.1106/152808302031067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Construction Textiles in Indoor Environmental Pollution

Abstract: Microbial contamination (mold, mildew, bacteria, fungus) is a leading cause of indoor environmental contamination and has generated serious concerns in the construction and building industries. Recent court cases in Texas and other states have required builders to redefine their role in dealing with the issue of microbial contamination during construction.Microbes are diverse, found everywhere, and highly adaptive. They cause shortand long-term problems within buildings through staining and deteriorating (corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…For this reason, we selected H 2 SO 4 . Since the boiling temperature of SO 4 2À is 337 C, setting the test temperature to 70 C did not create a constraint. Finally, the selected concentration was 0.3 mol/L, so that the pH level could be set to 0.5.…”
Section: Test Design Methodology For Aging Protocolmentioning
confidence: 98%
See 1 more Smart Citation
“…For this reason, we selected H 2 SO 4 . Since the boiling temperature of SO 4 2À is 337 C, setting the test temperature to 70 C did not create a constraint. Finally, the selected concentration was 0.3 mol/L, so that the pH level could be set to 0.5.…”
Section: Test Design Methodology For Aging Protocolmentioning
confidence: 98%
“…Furthermore, textiles are increasingly used as roofing membranes [4]. For example, many football stadiums have textile roofs, and a large number of stadiums will be built or renovated using textiles.…”
Section: Introductionmentioning
confidence: 99%
“…Sick Building Syndrome (SBS) emerged as an important concept, considering air quality, low-emission building materials, humidity control and thermal comfort. Buildings have been designed to minimize exposure to chemical substances and allergens to improve users' well-being [82][83][84].…”
Section: Evolution Of Building Priorities and Strategies Over Timementioning
confidence: 99%
“…In the early 2000s, increased concerns about climate change, including global warming, led to the priority of reducing greenhouse gas emissions from buildings. Efforts were focused on developing low-carbon facilities, incorporating technologies such as solar panels, energy recovery systems and sustainable construction strategies [85,86] to achieve energy savings, pollutant control and better performance [82].…”
Section: Evolution Of Building Priorities and Strategies Over Timementioning
confidence: 99%
“…Designers with green energy design competence and house owners presenting agreement with low-carbon life are the key factors in getting rid of pollution from interior environmental decoration. Air pollution and noise pollution from construction equipment (Sellappan and Janakiraman, 2014), pollution from building materials with chemical toxicant (Gerber and Yacoubian, 2002), and textiles building material pollution (White and Kuehl, 2002) are the common pollution in the interior environmental decoration of houses and the use process. Zheng et al (2011) pointed out the factors of ventilation performance, temperature, humidity, and interior pollution (Ojeda-Benítez et al, 2013); and, Lee and Levermore (2012) indicated that loft and wall insulation decreased internal air temperatures by up to 17% and low e glazing with louvres by up to 8%.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%